Infective endocarditis in right ventricular outflow tract conduits: a register-based comparison of homografts, Contegra grafts and Melody transcatheter valves. (29th January 2019) - Gröning, Mathis; Tahri, Naima Borg; Søndergaard, Lars; Helvind, Morten; Ersbøll, Mads Kristian; Ørbæk Andersen, Henrik
Abstract: OBJECTIVES: The aim was to investigate the incidence of infective endocarditis (IE) in right ventricle-to-pulmonary artery conduits implanted at a Danish tertiary centre. METHODS: Cases of IE in patients with homografts, Contegra grafts and Melody transcatheter valves were evaluated retrospectively with regard to the likeliness of the diagnosis using the modified Duke criteria and the likeliness of conduit involvement. Incidence rates for IE were calculated 1 and 5 years after valve implantation for all 3 conduits, and separately for Melody subgroups depending on which conduit served as landing zone. Cox regression with time-dependent covariates was used to model the impact of the conduit type on the incidence of IE. RESULTS: Annualized incidence rates of IE in homografts, Contegra grafts and Melody valves were 0.40% (0.40 cases per 100 patient-years), 0.97% and 6.96% 1 year and 0.27%, 1.12% and 2.89% 5 years after valve implantation. Hazard ratios (HRs) were 3.20 [95% confidence interval (CI) 0.91–11.17, P = 0.069] for Contegra grafts and 11.89 (95% CI 2.91–48.48, P < 0.001) for Melody valves compared to homografts. CONCLUSIONS: Bovine pulmonary conduits were more prone to endocarditis, with Melody valves being the most frequently infected. HRs for the risk of suffering from endocarditis were substantially higher for Melody valves and Contegra grafts compared to homografts, although this finding was only statistically significant for Melody valves and not for Contegra grafts.